Menggali Nilai Kemanusiaan dalam Tafsir Maqāṣid al-Qur’an Perspektif Hannān Lahhām - Qurroh A’yuniyah (Indonesian Journal Publisher, 2025)
Qur'anic interpretation in the contemporary era faces the challenges of humanitarian issues, such as gender justice and women's empowerment. Hannān Lahhām contributes significantly through maqāṣid al-Qur'an interpretation, emphasizing the importance of justice and the relevance of universal values. This study aims to explore Lahhām's approach in exploring humanitarian values and the relevance of his interpretation to modern challenges. Using the content analysis method, this study analyzes Lahhām's works, such as Maqāṣid al-Qur'an, as well as other supporting literature. Lahhām divides the Qur'anic maqāṣid into three main categories: maqāṣid khalq, maqāṣid al-qadr, and maqāṣid al-dīn. He successfully relates these values to contemporary issues, including gender justice and education, and offers a new paradigm in Qur'anic interpretation that is both normative and applicable.